Writing the Future: Basquiat and the Hip-Hop Generation - Kong-Perring, Sharon (Jazz Research Journal, 2022)
Writing the Future: Basquiat and the Hip-Hop Generation, Museum of Fine Arts, Boston, 18 October 2020–25 July 2021